Business Education Syllabuses for examinations in Principles of Business - Effective from 1987, Principles of Accounts - Effective from 1987, Bookkeeping - Effective from 1987 - Caribbean Examinations Council (Caribbean Examinations Council, 1987)
This document incorporates the original syllabus document and all amendments made to the syllabuses for Principles of Business, Principles of Accounts and Bookkeeping.
Keywords: CXC syllabus